Takaful’s medical products among international students in Malaysia - Ahmad Razimi, Mohd Shahril; Romle, Abd Rahim; Musa, Sulaiman Umar (IDOSI, 2017)
International students enrolled in Malaysian higher education institutions (HEI) incur two financial costs including the sum of tuition fees payable to receiving institutions and their study and living costs.A third and compulsory takaful or Islamic insurance contribution was recently integrated as another additional component of educational cost.Yet, majority of international students who do not have Islamic finance and banking established in their respective countries or do not have knowledge about of takaful (Islamic insurance) can hardly understand fully the concepts, operation and the benefits of the takaful.This paper is an attempt to compliment previous work by addressing the conceptual and operational differences between takaful and conventional insurance in relation to international students. Also the paper highlights some of the benefits that can be derived from group family takaful as one of the most important Islamic health insurance cover relevant to international students.